(untitled) (Czech Journal of International Relations, 2024)
Chiara Libiseller reviews Jakub Eberle and Jan Daniel’s timely book on the politics of Hybrid Warfare (HW) in Czechia. According to Libiseller, the book provides an insightful analysis of the detrimental effects of the HW discourse on democratic politics in Czechia. Leveraging a number of critical traditions, the book deepens the critique of the HW concept, which hitherto was often limited to aspects of conceptual clarity or newness. Yet, the authors’ engagement with the power of the concept could have gone even further: by examining these trends as unique to Czechia and as unique to the HW discourse, the authors remain unable to address the HW discourse’s international dimensions and its feeding on other militarizing discourses. Libiseller concludes that Eberle and Daniel’s book remains a powerful call to move away from Russia-centered narratives and reclaim agency to improve democratic and societal strength. Politics of Hybrid Warfare: The Remaking of Security in Czechia after 2014 Cham: Palgrave Macmillan, 2023, 229 pages, 978-3-031-32702-5.